Poranění sestupné hrudní aorty při blokové zlomenině žeber - Šmejkal, K; MarŠÍk, L; Šimek, J; Frank, M; DĚdek, T; PÁral, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2020)
The authors present a case of 74-year-old female patient who suffered a flail chest in motor vehicle accident. First day after injury a descending thoracic aorta was injured, most likely during manipulation with the patient. This injury was verified by operation, which was indicated 26 hours after the hospital admission, because of a sudden decrease of blood pressure with blood loss over 600 ml through the chest tube. The female patient died during surgery despite all efforts. Due to our experience with this rare case and after literature studying, we would recommend to consider early surgical revision. Based on the close contact of severely displaced sharp edges of ribs to the descending aorta, which was visible on the CT scan. Even through the absence of clear leak of contrast in the CT examination. We could resect these parts of ribs. Key words: flail chest, descending thoracic aortic injury.
Keywords: ženské pohlaví; paradoxní dýchání; počítačová rentgenová tomografie; Female; Thoracic Injuries; Ribs; Tomography, X-Ray Computed; lidé; žebra; poranění hrudníku; fraktury žeber; Aged; Flail Chest; Rib Fractures; Humans; senioři